2002
DOI: 10.1046/j.1365-2141.2002.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans retinoic acid prevents apoptosis of human marrow CD34+ cells deprived of haematopoietic growth factors

Abstract: Summary. The regulation of apoptosis plays a key role in haematopoiesis. It has been demonstrated that haematopoietic progenitor cells progressively undergo apoptotic cell death in the absence of appropriate growth factors. We studied the effects of pharmacological doses of all-trans retinoic acid (ATRA) on the apoptosis of human adult marrow CD34 + progenitor cells cultured for 7 d in a serum-free medium. We quantified CD34 + cells, clonogenic progenitors and 5 week colony-forming cells (CFC) before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…The African HIV-IC subtype can directly infect CD34+ hematopoietic progenitors[23]. Unlike previous studies[24,25] we found no association between dyserythropoiesis or apoptosis and altered cytokine levels or vitamin A deficiency[26,27], despite 90% of children having vitamin A deficiency[14]. More intensive investigations might identify cytokines that affect regulatory signals and could potentially be therapeutic targets to reduce hemopoietic inhibition in HIV patients.…”
Section: Discussioncontrasting
confidence: 67%
“…The African HIV-IC subtype can directly infect CD34+ hematopoietic progenitors[23]. Unlike previous studies[24,25] we found no association between dyserythropoiesis or apoptosis and altered cytokine levels or vitamin A deficiency[26,27], despite 90% of children having vitamin A deficiency[14]. More intensive investigations might identify cytokines that affect regulatory signals and could potentially be therapeutic targets to reduce hemopoietic inhibition in HIV patients.…”
Section: Discussioncontrasting
confidence: 67%
“…In the present study, however, we found that nestin expression in cord blood‐derived CD133 + cells increased with RA treatment. RA has been involved not only in embryonic development and neurogenesis (Niederreither et al, 2002) but also in survival of human bone marrow CD34 + cells in the absence of hematopoietic growth factors (Herault et al, 2002). Therefore, it is plausible that in the present study, RA played important roles in maintaining self‐renewal ability and promoting differentiation of hematopoietic stem cells to neural progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…RA also induces differentiation of embryonic stem cells into other types, including astrocytes, lung (Malpel et al, ), kidney (Mendelsohn et al, ), intestine (Plateroti et al, ), urothelium (Mauney et al, ), and pancreas (Micallef et al, ) in a time‐ and concentration‐dependent manner (Schuldiner et al, ). RA can maintain the survival of human bone marrow CD34‐positive cells in the absence of hematopoietic growth factors (Herault et al, ).…”
Section: Discussionmentioning
confidence: 99%